PERBUATAN HUKUM SANKSI ADAT PENYAMIL DI DESA PAKRAMAN TANGGAHAN PEKEN, DESA SULAHAN, KECAMATAN SUSUT, KABUPATEN BANGLI - Devi, Ni Made Radha Rani; Suta, I Made (VYAVAHARA DUTA, 2019)
Bali Customary Law is a law or regulation written with unwritten conditions that contain commands and prohibitions for the behavior of indigenous peoples in matters governed by human relations with God, human relations with the environment, and human relations with humans, which in Bali is known as dialogue Tri Hita Karana. The imposition of traditional sanctions is a way to restore balance or neutralize the shock caused by traditional violations that have taken place in the Pakraman village environment. Such as the imposition of the Penyamil Customary Sanction which was handed down because the community committed acts that violated the existing provisions in Desa Pakraman Tanggahan Peken. Based on this, the issues discussed in this study include: What legal actions can be imposed by the Penyamil Customary Sanction in Pakraman Tanggahan Peken Village, Sulahan Village, Susut District, Bangli Regency? The problems that arise are examined using the theory of validity and effectiveness of the law in dissecting the formulation of problems regarding legal actions that can be subject to Penyamil Customary Sanctions in the Village of Pakraman Tanggahan Peken, Sulahan Village, Susut District, Bangli Regency. Data collection in this study used interview techniques, literature study techniques, questionnaire distribution and observation. In this study, the type of research used is a type of empirical legal research. Penyamil Customary Penalty Occurrence in Desa Pakraman Tanggahan Peken due to harsh/dirty words and misbehavior in a holy place or in a village meeting, and because of this error aperson who is violated is subject to Penyamil Customary Sanction which can be in the form of financial penalties or Maprayascita fines , depending on the mistakes made. The factors that influence the occurrence of violations of the Penyamil Customary Sanction due to community ignorance, emotional, and developments in the current era of globalization.